EP.WE.453Impact of COVID 19 pandemic on colorectal rapid access investigations. (28th October 2021) - Maye, J; Sen, R; Sebastian, B; Ward, N; Athisayaraj, T
Abstract: Aim: The impact of the COVID-19 pandemic on delays in diagnosis of cancer has been highlighted at a national level. Such a delay represents an ongoing source of mortality and morbidity missing from the COVID-19 statistics. This study examines the delay in investigation of patients referred to the urgent colorectal cancer referral service at a single centre. Method: Retrospective data was collated from prospective database for all 1, 894 referrals to the urgent colorectal cancer referral service for the period 21 January to 24 December 2020. The time to appointment (TTA) was compared by date of referral and outcome type (endoscopy, CT abdomen pelvis (CT-AP), CT colonography (CT-C), clinic appointment). Results: Across 2020, fewer than 25% of patients met the NICE recommendation of appointment within 14 days (median TTA 30 days, first quartile 19). TTA increased dramatically in the first months of the pandemic (February median: 19; March: 80.5). TTA remained high, not falling below a median wait of 28 days until November. CT-C tests were particularly delayed (median TTA: 86) due to concerns regarding aerosol generation and COVID-19 transmission. Patients were offered CT-AP tests while awaiting their delayed CT-C, as CT-AP had a significantly better wait of 15 days. Conclusion: COVID-19 was a major disruptor of colorectal cancer diagnosis in 2020, with patients waiting more than twice as long as NICE recommends. This will likely continue into 2021, with further research required to assess the impact of this disruption on mortality and morbidity.